Anticholinergic and antioxidant activities of avocado (Folium perseae) leaves – phytochemical content by LC-MS/MS analysis. Issue 1 (1st January 2020) - Polat Kose, Leyla; Bingol, Zeynebe; Kaya, Ruya; Goren, Ahmet C.; Akincioglu, Hulya; Durmaz, Lokman; Koksal, Ekrem; Alwasel, Saleh H.; Gülçin, İlhami
ABSTRACT: In the first stage of the manuscript, we aimed to examine antioxidant capacity and anticholinergic properties of avocado ( Folium perseae ) leaves. Avocado leaf was extracted by water (WEFP) and ethyl alcohol (EEFP) and antioxidant activity was determined using by several antioxidant assays including DPPH· and ABTS + radical scavenging assays, Cu 2+ -Cu + reducing, Fe 3+ -Fe 2+ reducing, and FRAP reducing activities. Avocado leaf extracts demonstrated antioxidant activity and anticholinergic activities, while α-tocopherol, BHT, trolox, and BHA were used as positive antioxidant controls. In the second part of this study, the inhibition effects of WEFP and EEFP were valuated against acetylcholinesterase and butyrylcholinesterase enzymes, which catalyze the breakdown of choline esters (i.e. neurotransmitters). This study obviously showed that avocado leaf extracts had effective antioxidant, antiradical, and anticholinergic influences.